Sensory Characteristics of Robusta Wine Coffee (Coffea canephora L.) Seklotok with Different Fermentation Time - Setianingsih, Annisa; Nurdyansyah, Fafa; Muflihati, Iffah; Mahar Maligan, Jaya (Journal of Coffee and Sustainability, 2024)
Robusta coffee is the most widely produced type of coffee in Indonesia. About 87.1% of the total Robusta coffee production comes from Indonesia. However, not all types of Robusta coffee are included in the specialty coffee class. One of them is Seklotok robusta coffee with a natural process. It is necessary to do post-harvest processing that can improve the quality and taste of coffee. The wine process is one of the post-harvest coffee processes that can improve the taste because this process uses fermentation, which removes the slime layer and bitter taste and produces a mild impression on the coffee taste. This study aims to analyze and determine the effect of fermentation time on the sensory characteristics of Seklotok robusta wine coffee. Seklotok robusta coffee is fermented for 20 days, 30 days, and 40 days. Then, do the roasting and grinding. The results showed that Seklotok robusta wine coffee had a cupping score of 81.94–82.78. Fermentation treatment can improve the sensory characteristics of Seklotok robusta wine coffee so that it can be categorized as a specialty coffee.